Prevalence and possible predictors of the occurence of denture stomatitis in patients older than 60 years - Čanković, Miloš; Bokor-Bratić, Marija; Marinoski, Jovan; Stojanović, Dunja (Vojnosanitetski pregled, 2017)
Background/Aim. Denture stomatitis (DS) is one of the most common oral health problems among elderly population with removable dentures. Despite the high prevalence, etiology of the disease is not completely understood. It appears to be multifactorial, with a predominance of local factors. The aim of the study was to determine the prevalence and risk factors that contribute to the development of DS in upper removable denture wearers. Methods. This clinical study comprised three groups of subjects with upper removable dentures: the DS group, and the positive and negative control groups. Swab samples were taken from the tongue and palatal mucosa for microbiological examination. Data of denture age, dentures night wearing, unstimulated salivary flow rate (USFR) and saliva pH values were evaluated for all the participants. Results. The prevalence of DS was found to be 26.5%. Significantly higher values of overnight wearing (p = 0.000) and the mean age of dentures (p = 0.022) were found in the DS group compared to the controls. In relation to the positive mycological finding, a borderline significance difference among the groups was confirmed (p = 0.053). No significant association was found between DS and gender, age, the type of dentures, USFR, pH of saliva and bacteria findings. The patients who wore dentures at night had 26 times more chances to get DS compared to the patients who did not wear them overnight. Conclusion. This study confirms similar characteristics of DS prevalence in elderly population of Vojvodina compared to European. Continuous (overnight) wearing of dentures is considered to be major direct risk factor for DS development, while secondary role is attributed to denture age and oral Candida infection.
Keywords: dentures; stomatitis; denture; prevalence; candidiasis; oral; oral hygiene; preventive dentistry